The Didactic Dimension of Self-Efficacy Among Czech and Croatian Teacher Training Students Concerning Education about Puberty - Miluše Rašková; Dominika Provázková Stolinská; Michaela Bartošová (University of Zadar, 2023)
The paper presents the selected results of a research study of self-efficacy among students of teacher training for primary schools concerning education on puberty by comparing the Czech Republic and Croatia. The research was carried out as part of a student grant competition at Palacký University Olomouc1. Puberty is a significant element of sexuality education (Standards for Sexuality Education in Europe, 2010) which represents an important aspect in comprehensive education of children. It is important to prepare for this period in a timely and adequate manner, and this requires acquiring relevant knowledge. Primary school teachers must be prepared for puberty education in professional terms and in terms of their personality. The authors analysed the opinions about personal readiness of future primary school teachers in the didactic dimension of education which included the knowledge of the comprehensive definition of puberty; knowledge of basic topics of puberty education; knowledge of the goals of puberty education; respect for the humanizing aspects of puberty education; application of ethical principles in puberty education; selection of specific methods in puberty education; application of didactic approaches in puberty education and application of specific forms in puberty education. The results of the research study revealed how students (future teachers) felt with regard to being prepared for education on puberty in terms of some didactic dimensions, and whether they were sufficiently prepared for education in this specific area.